2015
DOI: 10.17576/jem-2015-4901-01
|View full text |Cite
|
Sign up to set email alerts
|

Market Concentration of Malaysia’s Islamic Banking Industry

Abstract: The aim of this paper is to evaluate the nature and changes of market concentration in the Malaysia's Islamic banking due to the restructuring of Islamic banking industry within the liberalization wave in the banking market. A total of 17 Islamic banks operating over the period of 2000-2010 had been considered. The structural approach framework was used to evaluate the nature and changes of market concentration in the Islamic banking industry in Malaysia. Under this approach, various market concentration index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…The author concluded that the predicted values were consistent with the observed values suggesting that the model was suitable for simulation of the experiment under the stated conditions with reasonable precision. The use of the model was also employed by Muhammad et al (2013) in conducting a microwave-assisted pyrolysis of palm kernel shell optimization, using RSM based on CCRD and concluded that RSM was capable of studying the pyrolysis of the samples under the stated conditions of 30 g mass of oil, 31.5 m reaction time and 100 ml/m nitrogen flow rate. The fact that the method was suitable for other areas of applications was supported by the work of Muazu et al (2012), who studied and developed a mathematical model for the transesterification of Jatropha curcas seed oil using factorial analysis to predict the optimal yield and concluded that the model was found suitable in predicting simulations under the conditions of the study.…”
Section: Introductionmentioning
confidence: 99%
“…The author concluded that the predicted values were consistent with the observed values suggesting that the model was suitable for simulation of the experiment under the stated conditions with reasonable precision. The use of the model was also employed by Muhammad et al (2013) in conducting a microwave-assisted pyrolysis of palm kernel shell optimization, using RSM based on CCRD and concluded that RSM was capable of studying the pyrolysis of the samples under the stated conditions of 30 g mass of oil, 31.5 m reaction time and 100 ml/m nitrogen flow rate. The fact that the method was suitable for other areas of applications was supported by the work of Muazu et al (2012), who studied and developed a mathematical model for the transesterification of Jatropha curcas seed oil using factorial analysis to predict the optimal yield and concluded that the model was found suitable in predicting simulations under the conditions of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Structural approach that uses structural information is employed to examine the nature of competition in the market. Many studies have used concentration ratios to investigate the level of competition in the banking market (Hakim & Chikr 2014;Mohammed et al 2015Mohammed et al , 2016Repon & Islam 2016). Meanwhile, nonstructural approach measures the degree of competition in the market directly without using any structural information about the market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicate that there is significant difference in perception of service quality among customers of Islamic banks on the basis of gender but there is no significant difference in service quality perception of male and female customers of conventional banks. Mohammed et al (2015) evaluated the nature and changes of market concentration in the Malaysia's Islamic banking due to the restructuring of Islamic banking industry within the liberalization wave in the banking market. This study found an evidence that structural changes in the Islamic banking market has changed the market structure of the respective market from moderately concentrated to low concentrated market; whereby supporting the existence of competitive environment in the Malaysian Islamic banking market.…”
Section: Introductionmentioning
confidence: 99%